Emergent Minimally Invasive Esophagogastrectomy - Thomas Fabian; Dorothy Chiaravalle; Jeremiah Martin (Case Reports in Surgery)
Introduction. Esophageal perforation in the setting of a malignancy carries a high morbidity and mortality. We describe our management of such a patient using minimally invasive approach. Methods. An 83-year-old female presented with an iatrogenic esophageal perforation during the workup of dysphagia. She was referred for surgical evaluation immediately after the event which occurred in the endoscopy suite. Minimally invasive esophagectomy was chosen to provide definitive treatment for both her malignancy and esophageal perforation. Results. Following an uncomplicated operative course, she was eventually discharged to extended care for rehabilitation and remains alive four years after her resection. Conclusion. Although traditional open techniques are the accepted gold standard of treatment for esophageal perforation, minimally invasive esophagectomy plays an important role in experienced hands and may be offered to such patients.